Profile sociodemographic, sociocultural and academic of nursing students in an institution of education private - Thaís Araújo da Silva; Genival Fernandes de Freitas (Universidad de Alicante, 2019)
This article aims to map and discuss the sociodemographic, sociocultural and academic profile of one ordinary student enrolled in a Nursing course linked to a Private High Education Institution in São Paulo city, Brazil. An exploratory-descriptive study was done, using a simple and not inferential statistic. It was revealed that the majority were female, originally from white ethnicity, married, belonging to evangelical groups, aged between 31 and 40 years; most of them have predominantly about four members in it's families; the family income is about one thousand and three thousand reais and the majority have economic dependence. The majority group was graduated in elementary/middle level in public schools; had a student scholarship during graduation; the largest number decided to choose nursing as the first choice. Most of them were brazilians; concentrated in the southeast region of the country and comes from the eastern region of São Paulo state; 26% used to watch television as the main leisure activity. This study may become an important tool in the restructuring of actions that address the demands of students and the nursing profession.